2021
DOI: 10.1111/jpg.12797
|View full text |Cite
|
Sign up to set email alerts
|

New Geochemical Insights Into Cenozoic Source Rocks in Azerbaijan: Implications for Petroleum Systems in the South Caspian Region

Abstract: The Maikop Group and the Diatom Formation constitute the two main source rocks in the South Caspian Basin and onshore Azerbaijan where large‐scale oil production began more than 150 years ago. However, the stratigraphic distribution of the source rocks and the vertical variation of source‐rock parameters are still poorly understood. The aim of the present paper is therefore to investigate in high resolution the source‐rock distribution in the Perekishkyul and Islamdag outcrop sections, located 25 km NW of Baku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In other words, the study of formation conditions of such rocks in previously known oil shale areas of Eastern Azerbaijan was not based on the methodological principles of the researches performed in this direction on a global scale, but at best, based on the hypotheses formed on the basis of analyzes of lithostratigraphic changes observed in the studied outcrop sections. However, in the few works published by foreign researchers together with local researchers (Baldermann et al, 2020;Aghayeva et al, 2021), more detailed studies were carried out in the study of two outcrops (Pirekeshkul and Islamdag sections). However, in these studies, oil shales found among the lithofacies of the sections were considered as argillaceous rocks.…”
Section: Or Abbasov Eocene-miocene Oil Shales In Azerbaijan: Stratigr...mentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the study of formation conditions of such rocks in previously known oil shale areas of Eastern Azerbaijan was not based on the methodological principles of the researches performed in this direction on a global scale, but at best, based on the hypotheses formed on the basis of analyzes of lithostratigraphic changes observed in the studied outcrop sections. However, in the few works published by foreign researchers together with local researchers (Baldermann et al, 2020;Aghayeva et al, 2021), more detailed studies were carried out in the study of two outcrops (Pirekeshkul and Islamdag sections). However, in these studies, oil shales found among the lithofacies of the sections were considered as argillaceous rocks.…”
Section: Or Abbasov Eocene-miocene Oil Shales In Azerbaijan: Stratigr...mentioning
confidence: 99%
“…In general, such oil shales contain diatoms and fossil fish, as well as an abundance of lamalginite and telalginite. The oil shales of the Upper Maikop section of the Islamdag are dominated by vitrinite and pyrite (Aghayeva et al, 2021). (Isaksen, et al, 2007) also stated that the organic-rich rocks of the Upper Maikop, selected from the mud volcanic area and outcrops, mainly contain organic matter of plant origin, consisting of spores and pollen, as well as amorphous and woody materials as secondary components.…”
Section: Or Abbasov Eocene-miocene Oil Shales In Azerbaijan: Stratigr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Outcrop studies in Azerbaijan (e.g. Washburn et al, 2019;Aghayeva et al, 2021) demonstrate that the main source rock within the western sector of the South Caspian Basin is the Oligocene-Miocene Maikop Group, with lesser contributions from Eocene source rocks. This is widely assumed also to be the case in the eastern, Turkmenistan, sector of the basin (Torres, 2007), but there is no direct evidence for this owing to the absence of pre-Pliocene outcrops or relevant well penetrations of the equivalent horizons here.…”
Section: Maikop Groupmentioning
confidence: 99%